Nanofiber mat spinal cord dressing-released glutamate impairs blood-spinal cord barrier - Sulejczak, Dorota; Taraszewska, Anna; Chrapusta, Stanisław J.; Dziewulska, Dorota; Nakielski, Paweł; Rafałowska, Janina (Folia Neuropathologica, 2016)
An excessive glutamate level can result in excitotoxic damage and death of central nervous system (CNS) cells, and is involved in the pathogenesis of many CNS diseases. It may also be related to a failure of the blood-spinal cord barrier (BSCB). This study was aimed at examining the effects of extended administration of monosodium glutamate on the BSCB and spinal cord cells in adult male Wistar rats. The glutamate was delivered by subarachnoidal application of glutamate-carrying electrospun nanofiber mat dressing at the lumbar enlargement level. Half of the rats with the glutamate-loaded mat application were treated systemically with the histone deacetylase inhibitor valproic acid. A group of intact rats and a rat group with subarachnoidal application of an ‘empty’ (i.e., carrying no glutamate) nanofiber mat dressing served as controls. All the rats were euthanized three weeks later and lumbar fragments of their spinal cords were harvested for histological, immunohistochemical and ultrastructural studies. The samples from controls revealed normal parenchyma and BSCB morphology, whereas those from rats with the glutamate-loaded nanofiber mat dressing showed many intraparenchymal microhemorrhages of variable sizes. The capillaries in the vicinity of the glutamate-carrying dressing (in the meninges and white matter alike) were edematous and leaky, and their endothelial cells showed degenerative changes: extensive swelling, enhanced vacuolization and the presence of vascular intraluminal projections. However, endothelial tight junctions were generally well preserved. Some endothelial cells were dying by necrosis or apoptosis. The adjacent parenchyma showed astrogliosis with astrocytic hypertrophy and swelling of perivascular astrocytic feet. Neurons in the parenchyma revealed multiple symptoms of degeneration, including, inter alia, perikaryal, dendritic and axonal swelling, and destruction of organelles. All the damage symptoms were slightly less severe in the rats given valproic acid treatment, and were absent from both the intact rats and the rats with ‘empty’ nanofiber mat dressing. These results demonstrate that glutamate-loaded nanofiber mat dressing can locally create glutamate levels capable of damaging BSCB and that the resulting damage can be mitigated with concurrent systemic valproate treatment.